1993
DOI: 10.1111/j.1746-1561.1993.tb06099.x
|View full text |Cite
|
Sign up to set email alerts
|

Chief State School Officers Rank Barriers to Implementing Comprehensive School Health Education

Abstract: Council of Chief State School Officers (CCSSO) members were surveyed to determine their perception of barriers to implementing comprehensive school health education. CCSSO members were asked to prioritize the barriers and offer recommendations to overcome the barriers. A structured response, paired-comparison survey instrument was developed and mailed to 56 of 57 CCSSO members. Eighty-two percent of the members responded. CCSSO members perceived lack of administrative commitment as the number one barrier. Lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Due to strong teacher preferences, only on‐line focus groups proved feasible. These limitations notwithstanding, multiple critical findings emerged that were consistent with previous research regarding CHES 5,20,24,25 and/or high‐stakes testing 7‐9 …”
Section: Discussionsupporting
confidence: 77%
“…Due to strong teacher preferences, only on‐line focus groups proved feasible. These limitations notwithstanding, multiple critical findings emerged that were consistent with previous research regarding CHES 5,20,24,25 and/or high‐stakes testing 7‐9 …”
Section: Discussionsupporting
confidence: 77%
“…With the exception of Teacher A, participants demonstrated minimal participation in a CSHP because of lack of time and support. Butler's (1993) study also revealed that the most influential barriers for successful implementation of a CSHP included insufficient time, money, and support.…”
Section: Emerging Themes In Beginning Health Teachers' Experiencesmentioning
confidence: 92%
“…However, the conceptual promise of a CSHP at this point in time outshines its practice. The promise of a CSHP is being affected by shrinking budgets, lack of resources, and inadequate support from staff, parents, and community; all of which are needed for successful implementation (Butler, 1993). In conjunction with participation in a CSHP, health teachers are also expected to be informed in the following: standards-based health curriculum frameworks (Joint Committee on National Health Education Standards, 1998), major health risk behavior categories (Centers for Disease Control and Prevention [CDC], 2004), skills-based curriculum (CDC, 1998), roles and responsibilities of entry-level health educators (National Commission for Health Education Credentialing Inc.…”
Section: The Many Roles Of An Effective Health Education Teachermentioning
confidence: 99%
“…One example of these recommendations is to create means to help coordinate efforts of government and nongovernment organizations to improve SHE. Other challenges might include the current crisis in our education system; 134,135 the complexity of education system reform; 136 the politicization of education, 137 public health, 138 and science; 139 the lack of administrative commitment for SHE; 140 We cannot do everything plausible to improve SHE. Without an analytic framework, rationale, and commitment, we may remain perpetually unfocused, indecisive, and inert.…”
Section: Question 7: What Are Major Challenges To Improving It?mentioning
confidence: 99%